About difficult process of understanding - Gauck, Joachim (Genocidas ir rezistencija, 1999)
When secret service, party and state archives were opened for the public in 1990, revealing a wealth of partially unknown facts, many GDR citizens were deeply distrustful of their own system, and stimulated discussions about the creation of Soviet socialism and their personal relationship with it.
Keywords: Germany; repressive structures; collaboration; Soviet Union; sovietization